2001
DOI: 10.1021/bm0101062
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Engineered tRNAs with an Extended 3‘ End by Exportin-t (Xpo-t) and Transport of tRNA-Attached Ribozymes to the Cytoplasm in Somatic Cells

Abstract: Our recent analysis indicates that the cytoplasmic localization of tRNA-attached ribozymes (tRNA-Rz) is critical for its high-level intracellular activity, suggesting that mature mRNAs in the cytoplasm are more accessible to ribozymes than pre-mRNAs in the nucleus (Kato et al. J. Biol. Chem. 2001, 276, 15378-15385; Kuwabara et al. Nucleic Acids Res. 2001, 29, 2780-2788). Although studies in Xenopus oocytes led to the proposal that only correctly processed mature tRNAs are exported from nuclei in a RanGTP-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Preliminary experiments suggested that a CD4 ϩ T cell line expressing the U5 EGS (560) molecule was protected from infection by a common laboratory strain of HIV-1 at a moi of 0.01 (28). Based on localization studies suggesting a nuclear locale for the RNase P enzyme, we hypothesized that inhibition of viral infection and subsequent cytopathology by the U5 EGS (560) molecule could occur at the level of incoming viral RNA, as well as RNA transcribed from integrated HIV-1 proviral DNA (5,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary experiments suggested that a CD4 ϩ T cell line expressing the U5 EGS (560) molecule was protected from infection by a common laboratory strain of HIV-1 at a moi of 0.01 (28). Based on localization studies suggesting a nuclear locale for the RNase P enzyme, we hypothesized that inhibition of viral infection and subsequent cytopathology by the U5 EGS (560) molecule could occur at the level of incoming viral RNA, as well as RNA transcribed from integrated HIV-1 proviral DNA (5,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Our PCR results must be tempered with the possibility that real-time PCR may not have the sensitivity to detect a limited number of integrated proviral HIV-1 genomes and that U5 EGS (560) inhibition of viral replication still occurs postintegration at the level of viral genome transcription. Another possibility would have the U5 EGS transcript transported to the cytoplasm of transfected cells following expression by the tRNA promoter and recruiting the RNase P enzyme to inhibit the generation of proviral DNA before reverse transcription of incoming viral RNA (5,33). Alternatively, RNase P-associated EGS molecules may bind to the U5 region of incoming HIV RNA and interfere with the initiation or completion of reverse transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Chimeric tRNAs with 3Ј-attached ribozymes (tRNA-Rzs) have been reported to be efficiently exported to the cytosol in somatic cells, but not in Xenopus oocytes (summarized in Kuwabara et al 2001). Based on exportin-t's substrate specificity (Arts et al 1998b;Lipowsky et al 1999), tRNA-Rz nuclear export would have been anticipated to be exportin-t-independent.…”
Section: Exportin-t/los1p-dependent Trna Nuclear Exportmentioning
confidence: 99%
“…1A). The intracellular activities of ribozymes depend on the level of expression of the ribozyme and the secondary structure of the target mRNA in cells (15±20, 24,25). Therefore, we chose to express ribozyme libraries under the control of the promoter of a human gene for tRNA Val , which can be expected to produce high-level expression of transcripts in cells.…”
Section: Resultsmentioning
confidence: 99%